This preview shows page 1. Sign up to view the full content.
Unformatted text preview: (a) proof (using induction) that [ a, ( a + ) n ] = n ( a + ) n1 n = 1 , 2 , 3 ,... (b) compute Z +  m ( x )( a) l n ( x ) dx with n ( x ) = * n ( x ) a + a n ( x ) = n n ( x ) R +  m ( x ) n ( x ) dx = mn...
View
Full
Document
This note was uploaded on 12/09/2011 for the course PHYS 460 taught by Professor Na during the Fall '11 term at Purdue UniversityWest Lafayette.
 Fall '11
 NA
 Physics

Click to edit the document details